Defensive medicine in Danish general practice. Types of defensive actions and reasons for practicing defensively - Merethe K. Andersen; Elisabeth Assing Hvidt; Kjeld M. Pedersen; Jesper Lykkegaard; Frans B. Waldorff; Anders P. Munck; Line B. Pedersen (Taylor & Francis Group, 2021)
Objective To examine the occurrence of and types of defensive medicine (DM), and the reasons for practicing DM in general practice. Design Prospective survey registration of consecutive consultations regarding defensive medicine defined as: Actions that are not professionally well founded but are carried out due to demands and pressure. The GPs registered the degree of defensiveness, the type(s) of defensive action(s) and the reason(s) for acting defensively. Setting Danish general practice. Subjects A total of 26 GPs registered a total of 1,758 consultations. Main outcome measures Defensive medical actions. Results Defensive actions were performed in 12% (210/1749) of all consultations. A fifth (46/210) of the defensive actions were characterised by the GPs as 'moderately' or 'highly' defensive. Frequent types of defensive actions were: blood tests, point-of-care-tests (POCTs) and referrals. Common reasons for defensive actions were: Influence from patients, 37% (78/210), concerns of overlooking severe disease, 32% (67/210) and influence from patient relatives, 12% (25/210). Conclusion Danish GPs registered self-perceived defensive actions in a prospective survey. DM was carried out in one out of eight consultations, most often due to patient influence. The most frequent defensive actions were blood tests, POCTs and referrals.